HUBUNGAN KONDISI OVERCROWDED DENGAN KETEPATAN PELAKSANAAN TRIASE DI INSTALASI GAWAT DARURAT - Ulpa, Resnani; Ari Wiryansyah, Oscar (Jurnal Kesehatan dan Pembangunan, 2025)
The Emergency Department (ER) is a vital part of the hospital that is tasked with providing first aid through the triage process to patients in emergency conditions. The increasing number of visits to the ER requires an appropriate patient priority selection system. This study aims to determine the relationship between overcrowded conditions and the accuracy of triage implementation in the ER of Siti Fatimah Hospital. The study used an analytical survey design with a cross-sectional approach, involving all 34 ER nurses selected through a total sampling technique. The research instrument used an observation sheet, and the data were analyzed using the chi square test. The results showed that 88.2% of nurses performed triage correctly and 11.8% did not. As many as 26.5% of nurses experienced overcrowded conditions. Statistical tests showed a significant relationship between overcrowded conditions and triage accuracy (p = 0.048). It is recommended that ER nurses be given special training to improve appropriate and measurable responses.